Beyond Histones: New Substrate Proteins of Lysine Deacetylases in Arabidopsis Nuclei - Füßl, Magdalena; Lassowskat, Ines; Née, Guillaume; Koskela, Minna M.; Brünje, Annika; Tilak, Priyadarshini; Giese, Jonas; Leister, Dario; Mulo, Paula; Schwarzer, Dirk; Finkemeier, Iris (Frontiers in Plant Science, 2018)
The reversible acetylation of lysine residues is catalyzed by the antagonistic action of lysine acetyltransferases and deacetylases, which can be considered as master regulators of their substrate proteins. Lysine deacetylases, historically referred to as histone deacetylases, have profound functions in regulating stress defenses and development in plants. Lysine acetylation of the N-terminal histone tails promotes gene transcription and decondensation of chromatin, rendering the DNA more accessible to the transcription machinery. In plants, the classical lysine deacetylases from the RPD3/HDA1-family have thus far mainly been studied in the context of their deacetylating activities on histones, and their versatility in molecular activities is still largely unexplored. Here we discuss the potential impact of lysine acetylation on the recently identified nuclear substrate proteins of lysine deacetylases from the Arabidopsis RPD3/HDA1-family. Among the deacetylase substrate proteins, many interesting candidates involved in nuclear protein import, transcriptional regulation, and chromatin remodeling have been identified. These candidate proteins represent key starting points for unraveling new molecular functions of the Arabidopsis lysine deacetylases. Site-directed engineering of lysine acetylation sites on these target proteins might even represent a new approach for optimizing plant growth under climate change conditions.